Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0188631
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma release assay for the diagnosis of latent tuberculosis infection: A latent-class analysis

Abstract: BackgroundAccurate diagnosis and subsequent treatment of latent tuberculosis infection (LTBI) is essential for TB elimination. However, the absence of a gold standard test for diagnosing LTBI makes assessment of the true prevalence of LTBI and the accuracy of diagnostic tests challenging. Bayesian latent class models can be used to make inferences about disease prevalence and the sensitivity and specificity of diagnostic tests using data on the concordance between tests. We performed the largest meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 164 publications
3
63
0
4
Order By: Relevance
“…In high‐burden settings and areas in which BCG vaccination is ubiquitous, the accuracy of the tuberculin skin test for the diagnosis of tuberculosis infection is controversial . TST and QFT test concordance test was poor, which was same as other regions with highest TB burden, where BCG are administered . In addition, our project site (Danyang county of Jiangsu province) is located close to the sea where nontuberculous Mycobacterium is highly prevalent.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In high‐burden settings and areas in which BCG vaccination is ubiquitous, the accuracy of the tuberculin skin test for the diagnosis of tuberculosis infection is controversial . TST and QFT test concordance test was poor, which was same as other regions with highest TB burden, where BCG are administered . In addition, our project site (Danyang county of Jiangsu province) is located close to the sea where nontuberculous Mycobacterium is highly prevalent.…”
Section: Discussionmentioning
confidence: 97%
“…21,28 TST and QFT test concordance test was poor, which was same as other regions with highest TB burden, where BCG are administered. [29][30][31][32][33][34] In addition, our project site (Danyang county of Jiangsu province) is located close to the sea where nontuberculous Mycobacterium is highly prevalent. In prior work from our province, we have shown that the prevalence of nontuberculous Mycobacterium is high.…”
Section: Discussionmentioning
confidence: 99%
“…IFN‐γ ELISA has been developed to assess CMI in TB and is one of the IFN‐γ IGRAs used for latent tuberculosis infection diagnosis . Although the clinical performance of IGRAs varies according to the characteristics of each study, it is superior to that of the tuberculin skin test in most cases . Furthermore, IFN‐γ ELISA has already been applied for VZV CMI assessment and is a rapid and simple quantitative method with high specificity and sensitivity for direct IFN‐γ detection by using whole blood rather than peripheral blood mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
“…26,[40][41][42] Although the clinical performance of IGRAs varies according to the characteristics of each study, it is superior to that of the tuberculin skin test in most cases. [43][44][45][46][47] Furthermore, IFN-γ ELISA has already been applied for VZV CMI assessment 21,24,25,32 and is a rapid and simple quantitative method with high specificity and sensitivity for direct IFN-γ detection by using whole blood rather than peripheral blood mononuclear cells. In the present study, VZVspecific CMI in response to a live attenuated HZ vaccine in individuals was assessed by an IFN-γ ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…The immunodiagnosis of Mycobacterium tuberculosis (MTB) infection was a new adjuvant method. The interferon-gamma release assay (IGRA) was one of the most important advances of immunodiagnosis, and has been widely applied and accepted in the clinic [4,5]. Enzyme-linked immunosorbent spot (ELISPOT) assay and enzyme-linked immunosorbent assay (ELISA), both through detecting released IFNγ in culture supernatants, are two forms of the IGRA.…”
Section: Introductionmentioning
confidence: 99%